Insights into AIE materials: A focus on biomedical applications of fluorescence - Ma, Junchi; Gu, Yanru; Ma, Depeng; Lu, Weizhao; Qiu, Jianfeng (Frontiers in Chemistry, 2022)
Aggregation-induced emission (AIE) molecules have garnered considerable interest since its first appearance in 2001. Recent studies on AIE materials in biological and medical areas have demonstrated that they show their promise as bio-materials for bioimaging and other biomedical applications. Benefiting from significant advantages of their high sensitivity, excellent photostability and good biocompatibility, AIE-based materials provide dramatically improved analytical capacities for in vivo detection and demonstration of vital biological processes. Herein we introduce the development history of AIE molecules and recent progress in areas of biotesting and bioimaging. Additionally, this review also offers an outlook for the potential applications of versatile AIE materials for tracing and treating pathological tissue, including overcoming challenges and feasible solutions.